PRASASTI MAYUNGAN DI DESA PAKRAMAN MAYUNGAN, DESA ANTAPAN, KECAMATAN BATURITI, KABUPATEN TABANAN - Prihandari, Ida Ayu Wayan (Humanis; Volume 4. No. 2. Agustus 2013)
This study aims at describing the research findings of Mayungan’s inscription from the aspects of linguistic, its contents and the perceptions of the rural community of Mayungan to the existence of the inscription. The Inscription of Mayungan is one of archaeological heritage in the village of Mayungan, Antapan Village, sub-district of Baturiti in the regency of Tabanan. This inscription was issued by one of the renowned king of Bali ancient time, Paduka Haji Jayapangus Arkajalancana with his two queens, Parameswari Indujaketana, and Mahadewi Sasangkajacihna in the year of saka 1103 or 1181 BC. Based on the findings the palaeography aspect used on the inscription of Mayungan is the ancient Balinese manuscript and most of the language used in this inscription is the ancient Javanese. It is similar to the other inscription wich were issued on the 11th – 12th BC. The rural community perceptions of the existence of the inscription is there was a genealogical ties between Mayungan villagers present and the past as it mentioned from the inscription, therefore the community are very protective of the existence of the inscription.
Keywords: the inscription, palaeography, perceptions.